2015
DOI: 10.5398/medpet.2016.39.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Carcass Production, and Meat Quality of Sumba Ongole Bulls Fed Ration Containing Velvet Bean (Mucuna pruriens)

Abstract: This research aimed to study performance, carcass production, meat quality, and economic feasibility of male Sumba Ongole cattle fed ration supplemented with velvet bean (M. pruriens). The research was designed in a completely randomized block design using 16 cattle with average body weight of 488+37.08 kg. The treatments were: T0= 15% straw + 85% concentrate; T1= T0 + 12% of velvet bean flour supplement; T2= T0 + 16% of velvet bean tempeh supplement; and T3= T0 + 200 mg/head/d of ractopamine hydrocloride. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…Although Bali cattle body frame is small, their carcass percentage was high about 52.72-57.6% (Hafid and Rugayah, 2009). This was higher than other Indonesia origin and local breed such as Peranakan Ongole (Ongole Grade) about 49,40%, SimPo (Croosbred of Simmental-Ongole Gradea) bout 51,18% (Carvalho et al, 2010), Madura cattle about 47% (Wiyatna, 2007) and Sumba-Ongole (SO) cattle about 55.25% (Yantika et al, 2016). USDA (2014) explained that beef carcass grade yield is influenced by layers of fat on rib, loin, rump, clod, flank, cod/udder and ribeye area.…”
Section: Introductionmentioning
confidence: 78%
“…Although Bali cattle body frame is small, their carcass percentage was high about 52.72-57.6% (Hafid and Rugayah, 2009). This was higher than other Indonesia origin and local breed such as Peranakan Ongole (Ongole Grade) about 49,40%, SimPo (Croosbred of Simmental-Ongole Gradea) bout 51,18% (Carvalho et al, 2010), Madura cattle about 47% (Wiyatna, 2007) and Sumba-Ongole (SO) cattle about 55.25% (Yantika et al, 2016). USDA (2014) explained that beef carcass grade yield is influenced by layers of fat on rib, loin, rump, clod, flank, cod/udder and ribeye area.…”
Section: Introductionmentioning
confidence: 78%
“…Although local cattle breeds did not significantly affect ADG (P> 0.05), but ADG on SO was higher than the three other breeds (P = 0.12), namely 1.24 kg. The ADG of SO recorded by Yantika et al, (2016) could reach 1-1.57 kg.…”
Section: Resultsmentioning
confidence: 86%
“…Local cattle breeds are known to have different performances. Sumba Ongole cattle have ADG of 0.8-1.5 kg/day, feed efficiency equal to 10-19%, and percentage of carcass equal to 51-56% (Agung et al 2015;Bata et al 2016;Yantika et al 2016). Bali cattle have ADG of 0.5-1 kg/day (Hau & Nulik 2017;Budiari et al 2020) with percentage of carcass equal to 50-54% (Suryanto et al 2017;Neno 2018;Priyono & Priyanto 2018) while Madura cattle have ADG of 0.2-0.6 kg/day (Wisnuwati et al 2014;Rab et al 2016) and percentage of carcass equal to 53% (Umar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MSM is naturally endowed with numerous ANFs primary among which is a high content of the toxic amino acid 3,4-dihydroxy-L-phenylalanine (L-DOPA) (Bhat 2011 ; Cacabelos 2017 ) as well as a high fibre content (9.7–19.3%) (Belewu and Olajide 2010 ). Whilst some of these ANFs can impart beneficial effects in animals especially at low dietary levels including antimicrobial and antioxidant attributes of condensed tannins (Bharadwaj et al 2021 ) as well as L-DOPA’s muscle building (Navegantes et al 2000 ), hypoglycemic, hypolipidemic, anti-cholesterolemic (Dharmarajan and Arumugam 2012 ; Ngatchic et al 2016 ), and meat quality enhancing (Yantika et al 2016 ) properties, these chemical substances can induce detrimental effects in broiler chickens. Indeed, previous studies have shown that dietary intake of mycotoxins DON and T-2 toxin (Huff et al 1986 ; Kubena et al 1988 , 1989 ), lipid peroxidised oils (Engberg et al 1996 ), and L-DOPA (Del Carmen et al 1999 ; Vadivel and Pugalenthi 2010 ) can induce performance and meat quality perturbations in the modern birds.…”
Section: Introductionmentioning
confidence: 99%